Collaborative Learning as a Leadership Tool: The Institutional Work of Writing Center Directors - Girgensohn, Katrin (Journal of Academic Writing, 2018)
Writing center directors have to face complex leadership tasks, but often do not have a background in management or administration studies. This study asks how they accomplish this demanding effort. Following a grounded theory approach, 16 writing centers in the USA were visited and expert interviews with the center directors were carried out. In bringing together the emerging concepts of the empirical work with the theoretical framework of the study of institutional work, this article shows that writing center directors transfer the pedagogy of writing centers to their leadership tasks. They use a stance of collaborative learning to deal with the challenges in their everyday work and to institutionalize their writing centers.